IMPACT OF COVID-19 PANDEMIC ON AMOUNT OF MUNICIPAL WASTE GENERATION – A CASE STUDY - Maksymilian Cieśla; Anna Kosior (Journal of Civil Engineering, Environment and Architecture, 2022)
This paper presents the results of research of the impact of the COVID-19 pandemic on the amount of municipal waste generated in the Sieniawa community (region of south-eastern Poland). The basic assessment was conducted in relation to restrictions and limitations introduced in Poland in order to limit the transmission of the SARS-CoV-2 virus. The pandemic affected almost every sector of the economy and disrupted the existing social life, including the functioning of the waste management system. The analysis shows that in the study area during the COVID-19 pandemic, the level of waste generated changed significantly. It has been shown that in the study area, the introduction of various types of restrictions (including working and/or studying remotely, "national quarantine", restrictions on free movement, etc.) contributed to a clear reduction in the amount of waste generated in households, business entities, educational institutions, commercial and service facilities, among others. It turned out that the results of our observations are opposed with the generally formulated theses in this aspect. Nevertheless, an undeniable and unintended (indirect) effect of the actions taken to combat COVID-19 was the reduction of negative human pressure on the environment (reduction of the amount of waste generated). It follows that, in the current state of knowledge, there are no unambiguous patterns developed which would make it possible to predict the mechanisms responsible for the amount of waste generated during a crisis situation.